Analisis Faktor-Faktor yang Mempengaruhi Minat Deposito Mudharabah di Bank Syariah Indonesia (BSI) di Jawa Timur - Fatikhul Islam, Akhlis; Yasin, Ach (Universitas Negeri Surabaya, 2025)
Islamic banking in Indonesia, especially in East Java, has enormous potential due to the dominant Muslim population that can contribute significantly to the regional economy. However, the level of public participation in using Islamic banking services, especially mudharabah savings, remains low. Therefore, an in-depth study is needed to understand the factors that influence the decision to choose mudharabah deposits in Bank Syariah Indonesia. The purpose of this study is to analyze the factors that can influence the interest of the people of East Java in using mudharabah deposits at Bank Syariah Indonesia (BSI). The method used is a quantitative approach with SEM-PLS analysis. Data was obtained through questionnaires distributed to the people of East Java, resulting in 289 samples for analysis. The results of the analysis indicate that interest in BSI mudharabah deposits is significantly influenced by the variables of attitude toward behavior, religiosity, and risk perception. On the other hand, the variables of subjective norm and perceived behavioral control have not been able to exert a significant influence on interest in BSI mudharabah deposits.